Memory Performance among Children with ADHD - Afsaneh Zarghi; Seyed Abolghasem Mehrinejad; Alireza Zali; Zahra Ramezankhani (Basic and Clinical Neuroscience, 2012)
Introduction: The present post-eventual research study was conducted with the purpose of comparing the memory performance between two distinct groups of 50 healthy children and 50 attention deficit hyperactivity disorder (ADHD) children (25 girls and 25 boys) in Tehran with an age range of 10-12.Methods.The whole students were selected through simple random sampling method and were assessed in children's medical center, the Clinic of Roozbeh Hospital, and Tehran's Andishe primary school (both girls' and boys' branches). The applied tools for data gathering were the Benton test and Wechsler memory sub-test (form A).Results:The results showed a significant difference between Benton test scores and Wechsler memory sub-test scores (i.e. personal and general information, orientation, mind control, logical memory, repeating numbers straightly or reversely, learning and memory) among healthy children and those with ADHD.Discussion:memory performance in children with ADHD was weaker than healthy children. In general, with regard to the memory deficit and attention disorder, these patients require both memory and attention rehabilitation for a better quality of l